Contribuciones del grupo de teatro “aquelarre” a las habilidades comunicativas de estudiantes universitarios - Toapanta Toaquiza, Katia Abigail (2018)
The need to enhance the students’ communication skills and the way in which theater intervenes in its development, allows analyzing a didactic function of human relationship in the social context. Therefore, it is necessary to understand language, body language, the codes and resources in which theater contributes to the strengthening of communication skills in university students. The theatrical art is a motivating axis that allows a scenography manifestation directed towards children, youth and adults, in order to generate new knowledge and change their way of thinking with the message that is transmitted after each work. In the same way people who do theater generates communication skills such as: expression, observation and empathic relationship, adopting a new sense of confidence inside and outside the group. In most universities, it is taken as an extracurricular activity. This research shows the importance of learning and study Theater. Hence, the main aim of this project is to determine: how Aquelarre theater group contributes in the strengthening of the communication skills in students of the Technical University of Cotopaxi? A qualitative approach was implemented by using techniques such as: focus group, non-participant observation and in-depth interview. The results obtained emphasize the importance of including theater within education since it help young people to obtain a favorable development in the classroom in which there is interaction between the teacher and the student. In conclusion, theater, more than strengthening the communication skills, is a dynamic where young people can stay relaxed. This research will be useful as research background for the students of different majors to deepen on this topic and take into account in order to include the theater within the educational network of the different universities of the country.